Method for preparing battery-grade iron phosphate by recovering iron phosphorus slag based on ultrasonic induced crystallization
Through the methods of inorganic acid leaching and ultrasonic induced crystallization, the problems of large reagent consumption and difficult wastewater disposal in the iron-phosphorus slag recovery process are solved, and the low-cost resource recycling and high-value utilization of iron and phosphorus elements in the iron-phosphorus slag are realized, thus improving the The quality of iron phosphate products.
Patent Information
- Application Number
- CN202411512318.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing iron-phosphorus slag recycling process has problems such as large reagent consumption, large amount of washing water and difficult to dispose of salt-containing wastewater, which makes it difficult to achieve high-value utilization of iron-phosphorus slag.
Inorganic acid is used to leach iron and phosphorus slag, and the pH is adjusted by diluting a small amount of water. Combined with ultrasonic induced crystallization, the acid-base usage and wastewater output are reduced, so as to achieve low-cost resource recycling and high-value utilization of iron and phosphorus elements in iron and phosphorus slag.
It has achieved low reagent consumption, circulating solution system, and low wastewater discharge, which has improved the quality of iron phosphate products and the high-value utilization of resources, and provided a new idea for iron phosphorus slag recycling.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing battery-grade ferric phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization, and in particular to a method based on an "inorganic acid leaching-ultrasonic induced crystallization-high temperature dehydration" process to achieve resource recovery and high-value utilization of iron and phosphorus in iron-phosphorus slag, belonging to the field of waste lithium-ion battery recycling and metallurgical environmental engineering. Background Art
[0002] Lithium iron phosphate has the advantages of high theoretical capacity, low cost, non-toxicity, good charge and discharge reversibility and high stability. It has become a promising lithium-ion battery cathode material and occupies a considerable share in the new energy vehicle and energy storage industries. However, as the service life of lithium iron phosphate batteries ends, the number of retired lithium iron phosphate batteries is bound to surge. Whether from the perspective of resources or the environment, the recycling of retired lithium iron phosphate batteries is imminent.
[0003] Since lithium is the most valuable element in retired lithium iron phosphate batteries, the recovery of lithium is of great significance for improving economic benefits. The selective recovery of lithium from battery waste containing lithium iron phosphate by oxidation leaching has become relatively mature and industrialized. However, the iron-phosphorus slag produced by oxidation leaching faces the problem of difficulty in achieving high-value utilization due to its poor recovery economy. Therefore, it is urgent to develop an efficient and clean recovery process for iron and phosphorus resources in iron-phosphorus slag to realize the resource utilization of iron-phosphorus slag.
[0004] Chinese patent CN 112520718 A discloses a method for selectively recovering battery-grade iron phosphate from iron-phosphorus slag acid leaching solution, that is, leaching iron-phosphorus slag with inorganic acid, then adding alkaline precipitant to selectively precipitate iron phosphate, and removing impurity metal elements at the same time. This method has the problem of consuming alkaline precipitant and difficult to handle precipitation mother liquor. Chinese patent CN113044824 A discloses a method for recycling waste iron phosphate, which takes a small part of iron-phosphorus solution to prepare iron phosphate precipitant, and then adds the iron phosphate precipitant to the remaining iron-phosphorus solution to react to obtain dihydrate iron phosphate precipitate, leaving part of the dihydrate iron phosphate precipitate as a precipitant for subsequent batch reactions, and the remaining dihydrate iron phosphate precipitate is made into anhydrous iron phosphate. This method only requires alkali solution in the preparation stage of the precipitant, which reduces the consumption of alkaline precipitant and is more environmentally friendly, but the process is complicated and has high requirements for production equipment.
[0005] Currently, the existing technologies for recycling iron-phosphorus slag to prepare battery-grade iron phosphate mostly have problems such as large reagent consumption, large amount of washing water, and difficulty in disposing of saline wastewater. Therefore, reducing reagent consumption and the generation of saline wastewater, reducing the amount of washing water, and improving the quality of iron phosphate products are issues that urgently need to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization, which uses inorganic acid to leach iron-phosphorus slag, adjusts pH and ultrasonically induces crystallization by diluting with a small amount of water, reduces the amount of acid and alkali and wastewater output, and realizes low-cost resource recovery and high-value utilization of iron and phosphorus elements in iron-phosphorus slag. The method has the advantages of low reagent consumption, circulatable solution system, less wastewater discharge, etc., provides a new idea for iron-phosphorus slag recycling, and has good application prospects.
[0007] To achieve the above purpose, the specific steps of the method are as follows:
[0008] (1) Leaching iron-phosphorus slag with inorganic acid, filtering after the reaction is completed to obtain a leachate containing iron and phosphorus;
[0009] (2) adding a certain amount of deionized water to the leachate for dilution, then raising the temperature, and performing a crystallization reaction with the assistance of ultrasound;
[0010] (3) After the crystallization reaction is completed, the ferric phosphate dihydrate precipitate and the crystallization mother liquor are obtained by filtration, wherein the crystallization mother liquor is concentrated and returned to step (1) for recycling, the ferric phosphate dihydrate is fully washed to remove the entrained impurities, and the washing water is returned to step (2) as dilution water, and then high-temperature dehydration is performed to obtain battery-grade anhydrous ferric phosphate.
[0011] Furthermore, the iron-phosphorus slag in step (1) is one or more of iron phosphate waste after lithium is extracted from lithium iron phosphate waste, iron phosphate waste after lithium is extracted from lithium iron phosphate pole pieces, iron phosphate waste after lithium is extracted from retired lithium iron phosphate batteries after disassembly, or iron phosphate waste after lithium is extracted from mixed black powder of positive and negative electrodes of retired lithium iron phosphate batteries, wherein the mass fraction of Fe element is 15-30%, and the mass fraction of P element is 13-20%.
[0012] Furthermore, the inorganic acid used for leaching in step (1) is one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, the inorganic acid concentration is 1-8 mol / L, the liquid-to-solid ratio is 2-10 mL / g, the leaching temperature is 25-65 °C, and the leaching time is 30-240 min.
[0013] Furthermore, the volume of deionized water added in step (2) is 0.2 to 2 times the volume of the leaching solution. If too much deionized water is added, the subsequent crystallization mother liquor concentration will be large and the energy consumption will be high; if too little deionized water is added, the pH of the solution will be low at the beginning of crystallization, making it difficult for iron phosphate to crystallize.
[0014] Furthermore, in step (2), the pH of the crystallization process is controlled to be 0.5-1.2, the temperature is 75-200°C, and the time is 20-240 min. If the pH of the crystallization process is too high, sufficient deionized water needs to be added, and subsequent concentration of the crystallization mother liquor is difficult; if the pH is too low, the solubility of ferric phosphate dihydrate increases, which is not conducive to crystallization.
[0015] Furthermore, the ultrasonic frequency used to assist crystallization in step (2) is 20-60 kHz, and the ultrasonic power is 20-100 W. If the ultrasonic frequency is too high, the system will be unstable and the crystal structure will be destroyed; if the frequency is too low, the nucleation process cannot be effectively stimulated, affecting the crystallization rate. If the ultrasonic power is too high, the energy consumption will increase and even cause the solution temperature to rise; if the power is too low, the number of nuclei will decrease and the crystallization rate will slow down. In general, too high an ultrasonic frequency / power will affect the crystal quality, while too low an ultrasonic frequency / power will affect the crystallization efficiency.
[0016] Furthermore, the crystallization mother liquor in step (3) is concentrated to the volume of the inorganic acid leaching agent in step (1), and then returned to step (1) for recycling as a leaching agent.
[0017] The method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization of the present invention has the following advantages compared with the prior art:
[0018] (1) Ultrasonic waves are used to assist the crystallization process. The cavitation effect of ultrasound is used to strengthen the crystallization nucleation process of the solution, and the crystallization rate of the crystallized product at low supersaturation concentration is improved. This not only avoids the use of alkaline precipitants from the source and reduces the discharge of alkaline wastewater, but also reduces the volume of deionized water added to the leaching solution during the crystallization process, so that the crystallization mother liquor can be concentrated and returned to the leaching process for recycling.
[0019] (2) Ultrasonic wave assisted crystallization was used to refine the grains by utilizing the dispersion effect of ultrasound, thereby improving the particle size and specific surface area of the ferric phosphate dihydrate crystal product, and achieving the regulation of the physical indicators of battery-grade iron phosphate from the precursor. DETAILED DESCRIPTION
[0020] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.
[0021] Example 1
[0022] The iron-phosphorus slag after lithium extraction from lithium iron phosphate waste was recovered, in which the mass fraction of Fe element was 24.43% and the mass fraction of P element was 12.50%. It was leached with 3.5 mol / L phosphoric acid, liquid-solid ratio was 5 mL / g, temperature was 65 ℃, time was 240min, and leaching solution was obtained after filtration. The leaching rates of iron and phosphorus were 98.84% and 98.69%, respectively. Subsequently, the leaching solution was mixed with 100 ml of deionized water, and ultrasonic assisted with a frequency of 40 kHz and a power of 80 W was used. It was kept warm at 70 ℃ for 150min, and the dihydrate iron phosphate precipitate was filtered, and its crystallization rate was 84.7%. The dihydrate iron phosphate product was washed, dried, and calcined to obtain anhydrous iron phosphate.
[0023] The characterization showed that the molar ratio of iron to phosphorus of the anhydrous ferric phosphate was 0.977, and the particle size (D 50 ) is 8.96 μm, and the specific surface area is 4.04 m 2 / g. The lithium iron phosphate cathode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 158.8 mAh / g at 0.1C. After 100 cycles at 1C, the capacity retention rate is 99.2%, reaching the battery grade standard. The crystallization mother liquor is concentrated and returned to the leaching process for recycling. After three cycles of use, the iron and phosphorus leaching rates, the crystallization rate of dihydrate iron phosphate, and the quality of the iron phosphate product remain stable.
[0024] Example 2
[0025] The iron-phosphorus slag after lithium extraction from the positive and negative electrodes of retired lithium iron phosphate batteries was mixed with black powder, in which the mass fraction of Fe element was 28.96% and the mass fraction of P element was 18.33%. It was leached with 8 mol / L phosphoric acid, liquid-solid ratio of 10 mL / g, temperature of 45°C, and time of 60 min. After filtration, the leaching solution was obtained, and the leaching rates of iron and phosphorus were 97.96% and 98.01%, respectively. Subsequently, 100 ml of the leaching solution was mixed with 200 ml of deionized water, and ultrasonic assisted with a frequency of 20 kHz and a power of 60 W was used. It was kept at a temperature of 200°C for 60 min, and the dihydrate iron phosphate precipitate was filtered, and its crystallization rate was 91.9%. The dihydrate iron phosphate product was washed, dried, and calcined to obtain anhydrous iron phosphate.
[0026] The anhydrous ferric phosphate has an iron-phosphorus molar ratio of 0.970 and a particle size (D 50 ) is 8.57 μm, and the specific surface area is 3.38m 2 / g. The lithium iron phosphate cathode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 158.2 mAh / g at 0.1C. After 100 cycles at 1C, the capacity retention rate is 98.8%, reaching the battery grade standard. The crystallization mother liquor is concentrated and returned to the leaching process for recycling. After three cycles of use, the iron and phosphorus leaching rates, the crystallization rate of dihydrate iron phosphate, and the quality of the iron phosphate product remain stable.
[0027] Example 3
[0028] The iron-phosphorus slag after dismantling and extracting lithium from retired lithium iron phosphate batteries, in which the mass fraction of Fe element is 17.53% and the mass fraction of P element is 13.29%, is leached with 2 mol / L sulfuric acid, liquid-to-solid ratio is 3 mL / g, temperature is 25 ℃, time is 180min, and the leaching solution is obtained after filtration. The leaching rates of iron and phosphorus are 98.05% and 98.44%, respectively. Subsequently, 100 ml of the leaching solution is mixed with 200 ml of deionized water, and ultrasonic assisted with a frequency of 60 kHz and a power of 100 W is used. It is kept at 100 ℃ for 240 min, and filtered to obtain a dihydrate iron phosphate precipitate with a crystallization rate of 90.4%. The dihydrate iron phosphate product is washed, dried, and calcined to obtain anhydrous iron phosphate.
[0029] The anhydrous iron phosphate has an iron-phosphorus molar ratio of 0.965 and a particle size (D 50 ) is 7.55 μm, and the specific surface area is 4.04m 2 / g. The lithium iron phosphate cathode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 160.1 mAh / g at 0.1C. After 100 cycles at 1C, the capacity retention rate is 99.4%, reaching the battery grade standard. The crystallization mother liquor is concentrated and returned to the leaching process for recycling. After three cycles of use, the iron and phosphorus leaching rates, the crystallization rate of dihydrate iron phosphate, and the quality of the iron phosphate product remain stable.
[0030] Example 4
[0031] The iron-phosphorus slag after lithium extraction from the lithium iron phosphate pole piece was recovered, in which the mass fraction of Fe element was 25.93% and the mass fraction of P element was 17.36%. It was leached with 4 mol / L hydrochloric acid, a liquid-solid ratio of 5 mL / g, a temperature of 40 ℃, and a time of 120 min. After filtration, the leaching solution was obtained, and the leaching rates of iron and phosphorus were 98.49% and 98.98%, respectively. Subsequently, 100 ml of the leaching solution was mixed with 80 ml of deionized water, and ultrasonic assisted with a frequency of 45 kHz and a power of 75 W was used. It was kept warm at 90 ℃ for 90 minutes, and the dihydrate iron phosphate precipitate was filtered, and its crystallization rate was 89.5%. The dihydrate iron phosphate product was washed, dried, and calcined to obtain anhydrous iron phosphate.
[0032] The anhydrous ferric phosphate has an iron-phosphorus molar ratio of 0.968 and a particle size (D 50 ) is 5.90 μm, and the specific surface area is 5.85m 2 / g. The lithium iron phosphate cathode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 159.6 mAh / g at 0.1C. After 100 cycles at 1C, the capacity retention rate is 99.5%, reaching the battery grade standard. The crystallization mother liquor is concentrated and returned to the leaching process for recycling. After three cycles of use, the iron and phosphorus leaching rates, the crystallization rate of dihydrate iron phosphate, and the quality of the iron phosphate product remain stable.
[0033] Comparative Example 1
[0034] The raw materials and experimental process are the same as those in Example 1, except that after the leaching solution and deionized water (100 ml each) are mixed, ultrasonic assistance is not performed, and the mixture is kept at 70°C for 150 minutes, and then filtered to obtain a precipitate of ferric phosphate dihydrate, the crystallization rate of which is 19.4%. The ferric phosphate dihydrate product is washed, dried, and then calcined to obtain anhydrous ferric phosphate.
[0035] The anhydrous ferric phosphate has an iron-phosphorus molar ratio of 0.964 and a particle size (D 50 ) is 23.40 μm, and the specific surface area is 1.18 m 2 / g. The lithium iron phosphate positive electrode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 139.3 mAh / g at 0.1C, and a capacity retention rate of 90.7% after 100 cycles at 1C. Compared with Example 1, the crystallization rate of dihydrate iron phosphate is significantly reduced in Comparative Example 1. This indicates that the cavitation effect of ultrasound strengthens the crystallization nucleation process of the solution and improves the crystallization rate of the crystallized product at low supersaturation concentration.
[0036] Comparative Example 2
[0037] The raw materials and experimental process are the same as those in Example 1, except that the ultrasonic frequency used is 15 kHz, the power is 15 W, and the temperature is kept at 70°C for 150 minutes. The precipitate of dihydrated iron phosphate is obtained by filtration, and its crystallization rate is 30.5%. The dihydrated iron phosphate product is washed, dried, and then calcined to obtain anhydrous iron phosphate.
[0038] The anhydrous ferric phosphate has an iron-phosphorus molar ratio of 0.969 and a particle size (D 50 ) is 16.96 μm, and the specific surface area is 1.98 m 2 / g. The lithium iron phosphate positive electrode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 142.5 mAh / g at 0.1C, and a capacity retention rate of 98.4% after 100 cycles at 1C. Compared with Example 1, the crystallization rate of iron phosphate dihydrate in Comparative Example 2 is lower. This indicates that the ultrasonic frequency and power are too low, which will lead to the inability to effectively stimulate the nucleation process and affect the crystallization rate.
[0039] Comparative Example 3
[0040] The raw materials and experimental process are the same as those in Example 1, except that the ultrasonic frequency used is 70 kHz, the power is 110 W, and the temperature is kept at 70°C for 150 minutes. The precipitate of dihydrated iron phosphate is obtained by filtration, and its crystallization rate is 89.1%. The dihydrated iron phosphate product is washed, dried, and then calcined to obtain anhydrous iron phosphate.
[0041] The anhydrous ferric phosphate has an iron-phosphorus molar ratio of 0.967 and a particle size (D 50 ) is 6.39 μm, and the specific surface area is 4.07m 2 / g. The lithium iron phosphate cathode material prepared with the anhydrous iron phosphate as a precursor has a discharge specific capacity of 155.8 mAh / g at 0.1C, and a capacity retention rate of 85.7% after 100 cycles at 1C. Compared with Example 1, the crystallization rate of iron phosphate dihydrate in Comparative Example 3 is slightly lower. This shows that excessive power and frequency of ultrasound will not cause a continuous increase in the crystallization rate, but will increase energy consumption. At the same time, excessive ultrasound will cause damage to the material structure, affecting the electrochemical cycle performance of the synthetic material.
[0042] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization, characterized in that: The steps of the method are as follows: (1) Leaching iron-phosphorus slag with inorganic acid, filtering after the reaction is completed to obtain a leachate containing iron and phosphorus; (2) adding deionized water to the leachate to dilute it, then raising the temperature, and performing a crystallization reaction with the assistance of ultrasound; (3) After the crystallization reaction is completed, the ferric phosphate dihydrate precipitate and the crystallization mother liquor are obtained by filtration, and the volume of the crystallization mother liquor is concentrated to the volume of the inorganic acid leaching agent in step (1), and then returned to step (1) for recycling as a leaching agent; the ferric phosphate dihydrate is fully washed to remove entrained impurities, and the washing water is returned to step (2) as dilution water, and then high-temperature dehydration is performed to obtain battery-grade anhydrous ferric phosphate.
2. The method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization according to claim 1, characterized in that: The iron-phosphorus slag in step (1) is one or more of iron phosphate waste after lithium is extracted from lithium iron phosphate waste, iron phosphate waste after lithium is extracted from lithium iron phosphate pole pieces, iron phosphate waste after lithium is extracted from retired lithium iron phosphate batteries after disassembly, or iron phosphate waste after lithium is extracted from mixed black powder of positive and negative electrodes of retired lithium iron phosphate batteries; the mass fraction of Fe element in the iron-phosphorus slag is 15-30%, and the mass fraction of P element is 13-20%.
3. The method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization according to claim 1, characterized in that: The inorganic acid used for leaching in step (1) is one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, the inorganic acid concentration is 1-8 mol / L, the liquid-to-solid ratio is 2-10 mL / g, the leaching temperature is 25-65 °C, and the leaching time is 30-240 min.
4. The method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization according to claim 1, characterized in that: In step (2), the volume of deionized water added is 0.2 to 2 times the volume of the leaching solution.
5. The method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization according to claim 1, characterized in that: In step (2), the pH of the crystallization process is controlled to be 0.5-1.2, the temperature is 75-200°C, and the time is 20-240 min.
6. The method for preparing battery-grade iron phosphate by recycling iron-phosphorus slag based on ultrasonic induced crystallization according to claim 1, characterized in that: The ultrasonic frequency used to assist crystallization in step (2) is 20-60 kHz, and the ultrasonic power is 20-100 W.
Citation Information
Patent Citations
Method for selectively recovering battery-grade iron phosphate from lithium extraction residue pickle liquor
CN112520718A
Iron phosphate waste cyclic regeneration method and application thereof
CN113044824A
Method for ultrasonic preparation of nano iron phosphate of lithium iron phosphate
CN104505495A
Method for recovering nanometer iron phosphate from lithium iron phosphate battery
CN109250696A
Method for recovering iron phosphate slag after lithium extraction of battery
CN117069081A
Cited By
Method for improving struvite crystallization rate and purity based on ultrasonic pretreatment
CN120364892A
Method for regenerating iron phosphate with high iron-phosphorus ratio from lithium iron phosphate extraction slag
CN120573669A
Method for recovering iron phosphate from black powder acid leaching residues of retired lithium iron phosphate batteries
CN121269653A